PENERAPAN PROBLEM BASED LEARNING BERBASIS LESSON STUDY UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR KOGNITIF SISWA KELAS X MIA MADRASAH ALIYAH MUHAMMADIYAH 1 MALANG TAHUN PELAJARAN 2014/2015 PADA MATA PELAJARAN BIOLOGI - Muh. Zaini Hasanul Muttaqin; Ikhwanul Azmi (LPPM Institut Pendidikan Nusantara Global, 2020)
The Based on observations and interviews with biology teacher grade X MIA MA Muhammadiah 1 Malang the problem that arises is the learning activities of students in following the lessons are very minimal and the student's learning outcomes are relatively low. The solution to improve students' activeness and learning outcomes is to apply PBL. Based on the data that has been analyzed, it can be concluded that the application of PBL through LS can increase the activeness of students' learning. This can be seen from the percentage of classical student learning activeness in the first cycle of 67.56 % increased to 75.62% in the second cycle. Then the application of PBL can improve student learning outcomes as seen from the cognitive learning outcomes of students in the first cycle the number of students whose grades have not reached KKM as much as 8, and in the second cycle the number of students who have not reached kkm as many as 2 students.